Prepaid Electricity Marketing Communication Strategy at PT. PLN (Persero) Temanggung Customer Service Unit - Muhammad Hasan Absori; Deni Ramdani (AFEBI Management and Business Review, 2020)
PT. PLN (Persero) is a provider of electrical energy services in Indonesia. Technological developments encourage the innovation of prepaid electricity programs in providing effective and efficient services to consumers. So marketing communication is one of the strategies used to introduce prepaid electricity products to the public. marketing communication is communication that is used to improve marketing strategies in expanding the target market segmentation. PT. PLN (Persero) Temanggung Customer Service Unit uses socialization techniques in delivering prepaid electricity programs to the Temanggung community. The purpose of this study was to determine the form of marketing communication channels used by PT. PLN (Persero) Temanggung Customer Service Unit to provide prepaid electricity program information to consumers in order to increase prepaid electricity usage in Temanggung. This study uses a qualitative description method. Research data obtained by interview and observation conducted at PT. PLN (Persero) Temanggung Customer Service Unit. In this study conducted with triagulation techniques. The research results of PT. PLN (Persero) Temanggung Customer Service Unit uses marketing communication channels in promoting prepaid electricity programs. The message delivered contains the difference between prepaid and postpaid electricity, benefits, token costs or electricity energy vouchers and how to purchase tokens on the prepaid electricity program.